HISTOLOGICAL STUDY OF ETAWAH CROSSBRED LUNG - Semarabawa, I Gede; Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2021)
The aim of this research is to know about the histological structure and morphometry of lungs from the etawah crossbreed. This research used 64 samples taken from both young and adult Etawah crossbred goats and then made histology preparations. The histology preparations are colored by the Harris-Hematoxylin Eosin method.  The results showed that the histological structure of the lungs of etawah crossbred goats was mostly composed of the alveoli, wrapped by the capsule, and in it was found bronchial and bronchioles. There are no differences in lung capsule thickness within male and female etawah crossbred goats for both young and adult ages (P>0.05), but the visceral pleura in female goats is denser than in adults.  The bronchus contours of the male goats were larger (P<0.05) than females at both young and adult goats. Etawah crossbred male goat’s lungs have more hyaline cartilage than females with flat forms where on the male it is elongated beyond adventitia whereas in female is round. Bronchioles contours in adult goats is larger (P<0.05) than in the female. On the other side, the bronchioles contour in young female goats is larger. The smooth muscles of males' bronchioles are circular with clear boundaries, while on females, its boundaries are not clear and discontinuous.